Evaluation for Suitability of Urban Roof Greening in Arid Areas of Northwest China - Benteng Liu, Yuhui Wang, Zhiwei Yang, Ke Ma, Yuqing Zhou (Forest Chemicals Review, 1970)
Roof greening is an effective method which can improve urban ecological environment, and the suitability evaluation of roof greening is of great significance to improve the quality of human dwelling environment in semi-arid areas of Northwest China. Firstly, five factors including cost attribute, building attribute, roof attribute, greening attribute and facility attribute were chosen in this paper to construct the suitability evaluation index system of urban roof greening in semi-arid area of Northwest China. Secondly, the AHP was used to calculate the weight, and the multi-level fuzzy analysis method was used to establish the suitability evaluation model of urban roof greening. Finally, the suitability evaluation of 32 samples of urban roof greening in Lanzhou was conducted. The results indicated that only 2 samples were in the suitable grade, 8 samples were in the grade secondary to suitable grade, 22 samples were in the unsuitable grade, and the overall suitability degree of the samples was low. The suitability evaluation index system of roof greening has strong applicability for semi-arid areas of Northwest China, and the research results are expected to provide decision-making basis for urban artificial ecosystem construction in semi-arid areas.